Trade between India and Southeast Asia: A Historical Study: The Impact of International Trade on the Socio-economic Development of Southeast Asia (Journal of Advances and Scholarly Researches in Allied Education, 2018)
International trade has been a crucial element of the long-term economic development of Southeast Asia. Involvement in international trade has laid crucial foundations for the present-day economic process of this region since the fourth quarter of the 20th century. This article aims to provide a general overview of the relations between international trade and the economy of Southeast Asia from a long-term perspective. First, a brief description is supplied about the relationships between natural endowments and international trade of Southeast Asia before the European arrival. This article traced the role of international trade in Southeast Asia’s long-term path to socio-economic development, by dividing the region’s history in accordance with changing relationships between trade and the economy and society. The relationships are strong, and therefore the economic development of Southeast Asia has been influenced by the changing trend of international trade. The region is found between China and India, both of which had been powerful economic forces, and has been economically and culturally influenced by the 2 civilizations. When Europeans participated in the trade of Southeast Asia within the early sixteenth century, the Southeast Asian economy was faced with greater demand for primary products. The high demand from outside Southeast Asia served as a robust motivation for socio-economic changes within the region.